2015
DOI: 10.1111/resp.12649
|View full text |Cite
|
Sign up to set email alerts
|

Symptom‐based management of the idiopathic interstitial pneumonia

Abstract: The term 'idiopathic interstitial pneumonia' (IIP) encompasses a wide variety of diseases with different and often unexplained pathophysiology as well as diverse natural histories. Unfortunately, many of these diseases are progressive and some are poorly responsive to available therapies. Despite the varied nature of IIPs, patients experience common symptoms related to their chronic lung disease. Dyspnoea, cough, fatigue and depression contribute substantially to morbidity and are often difficult to manage. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 80 publications
0
35
0
Order By: Relevance
“…Patients with cancer diagnoses were the next studied population of focus (n=13), [38][39][40][41][42][43][44][45][46][47][48][49][50] followed by patients with interstitial lung disease (n=8), [51][52][53][54][55][56][57][58] and lastly one study focussed on patients with Huntington's disease (Table 1) Page S35…”
Section: Resultsmentioning
confidence: 99%
“…Patients with cancer diagnoses were the next studied population of focus (n=13), [38][39][40][41][42][43][44][45][46][47][48][49][50] followed by patients with interstitial lung disease (n=8), [51][52][53][54][55][56][57][58] and lastly one study focussed on patients with Huntington's disease (Table 1) Page S35…”
Section: Resultsmentioning
confidence: 99%
“…However, correlations between FVC and the CAT score were not seen in subgroups. Recent findings demonstrated that quality of life was not consistent with pulmonary function tests in subjects with interstitial lung disease [5,13]. This discordance was likely because of fatigue and deconditioning due to dyspnea and cough, or subjects' reduced awareness of deterioration in actual pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, according to the paradigm shift, palliative care methods were addressed for all stages of chronic respiratory disease. For example, structured communication between healthcare professionals and patients was vital to ensure the best possible support and treatment [5,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Olukogbon et al measured the breathing patterns in IPF patients and found that resting ventilation rate increased with worsening disease severity and declining lung function. 17 These changes were also associated with increased dyspnoea and cough severity, thus providing a quantifiable link between symptoms and disease severity.…”
Section: Treating Ildmentioning
confidence: 99%